Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation

Waxes composition of Quercus suber reproduction cork from different Spanish provenances - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (Wood Science and Technology, 1999)
The chemical composition of waxes was studied in Quercus suber cork planks collected in seven localities of the three main production areas of Spain. Waxes were extracted with chloroform (CHCl3 ) and the extract was submitted to saponi®cation in order to obtain the neutral and acid fractions. The trimethylsilyl derivatives of both fractions were analysed by GC-MS. The seven populations cannot be distinguished by their total contents of waxes (Chloroform extract) and of the neutral and acid fraction. This lack of differences could be due to the important variability among samples of each population. The neutral fraction was mainly composed of fatty alcohols (all the even members from C18 to C26 , with traces of the intermediate odd members and some unsaturated groups) and triterpenes (11 components, among them friedelin, betulin and cerin were identi®ed) and a very small amount of monocarboxylic fatty acids (C16 and C24 members) was also present. The main group of compo- nents of the acid fraction was that of fatty acids (saturated even C14±C24 and odd C15 , C17 , C21 members, accompanied by a great amount of unsaturated terms and some x-hydroxyacids, 18-hydroxy-9,12-octadecadienoic and 18-hydroxy-9-oct- adecenoic acids). Four triterpenes and the C20 and C24 alcohols were also detected in the acid fraction. Signi®cant differences were found among the corks of the various provenances in the global contents of alcohols and triterpenes and in these individual components contents of the neutral fraction. Concerning the differences among the various provenances in the contents of the groups of fatty acids, alcohols, and triterpenes in the acid fraction, a higher number of differ- ences were obtained in the comparisons of the contents of acids and triterpenes, whereas the differences were practically null in the case of the alcohols. When the differences were studied considering the individual compounds, the relation with the behaviour of the contents of the groups of components was not as clear as it happens in the neutral fraction. In this case, the differences were scarcer and they did not show a unique pattern, neither in the components, nor the populations. There is no correspondence in the differences among the provenances regarding the components of the neutral fraction or those of the acid fraction. No clear relationship was found between the geographical proximity of the provenances and chemical similarity of the waxes composition.
Keywords: Acid fraction; component (voyant); Cork; neutral fraction; provenance; waxes